Comparative Analysis of the Mucosal Adjuvanticity of the Type II Heat-Labile Enterotoxins LT-IIa and LT-IIb - Martin, Michael (American Society for Microbiology, 2000)
Cholera toxin (CT) and the heat-labile enterotoxin of Escherichia coli (LT-I) are members of the serogroup I heat-labile enterotoxins (HLT) and can serve as systemic and mucosal adjuvants. However, information is lacking with respect to the structurally related but antigenically distinct serogroup II HLT, LT-IIa and LT-IIb, which have different binding specificities for ganglioside receptors. The purpose of this study was to assess the effectiveness of LT-IIa and LT-IIb as mucosal adjuvants in comparison to the prototypical type I HLT, CT. BALB/c mice were immunized by the intranasal (i.n.) route with the surface protein adhesin AgI/II of Streptococcus mutans alone or supplemented with an adjuvant amount of CT, LT-IIa, or LT-IIb. Antigen-specific antibody responses in saliva, vaginal wash, and plasma were assayed by enzyme-linked immunosorbent assay. Mice given AgI/II with LT-IIa or LT-IIb by the i.n. route had significantly higher mucosal and systemic antibody responses than mice immunized with AgI/II alone. Anti-AgI/II immunoglobulin A (IgA) antibody activity in saliva and vaginal secretions of mice given AgI/II with LT-IIa or LT-IIb was statistically similar in magnitude to that seen in mice given AgI/II and CT. LT-IIb significantly enhanced the number of AgI/II-specific antibody-secreting cells in the draining superficial cervical lymph nodes compared to LT-IIa and CT. LT-IIb and CT induced significantly higher plasma anti-AgI/II IgG titers compared to LT-IIa. When LT-IIb was used as adjuvant, the proportion of plasma IgG2a relative to IgG1 anti-AgI/II antibody was elevated in contrast to the predominance of IgG1 antibodies promoted by AgI/II alone or when CT or LT-IIa was used. In vitro stimulation of AgI/II-specific cells from the superficial lymph nodes and spleen revealed that LT-IIa and LT-IIb induced secretion of interleukin-4 and significantly higher levels of gamma interferon compared to CT. These results demonstrate that the type II HLT LT-IIa and LT-IIb exhibit potent and distinct adjuvant properties for stimulating immune responses to a noncoupled protein immunogen after mucosal immunization.